Values based education: implementation of character education through adab, tahfidz and science program at MIM Baleharjo Pacitan - Astuti, Tri Puji; Wahyuningsih, Diah (At-Tajdid: Jurnal Ilmu Tarbiyah, 2024)
Values based education has become major concern in building character, especially for younger generation. This article explores implementation of character education through integration of politeness, tahfidz (spiritual memorization), and science learning programs. Research methods used include literature analysis and case studies to examine impact of these programs on student character formation. The findings suggest integration of modesty, tahfidz, and science learning programs can serve as strong foundation for building ethical and strong character. Adab program focuses on promoting good behavior and ethics, because adab program plays an important role in helping students understand ethics and good behavior when interacting with friends or other people. Meanwhile, tahfidz program strengthens spiritual values and obedience, helps shape students' pious character, which leads to improved behavior, discipline, enthusiasm for learning, and self-confidence, instill love Al-Qur'an and knowledge of religious practices. Additionally, science learning gives students deep understanding of universe and encourages critical and creative thinking. Science learning encourages students to think creatively, there are providing space for students to generate new ideas, explore alternative approaches, and develop innovative solutions to complex challenges. Integration of these three programs creates holistic and integrated learning environment, enabling students to develop as responsible and ethical individuals.